The Role of Hip Abductor Strength in Identifying Older Persons at Risk of Falls: A Diagnostic Accuracy Study - Gafner SC (Dove Medical Press, 2020)
Simone Chantal Gafner,1,2 Caroline Henrice Germaine Bastiaenen,2 Serge Ferrari,3 Gabriel Gold,4 Andrea Trombetti,5 Philippe Terrier,6,7 Roger Hilfiker,8 Lara Allet1,8,9 1Geneva School of Health Sciences, HES-SO University of Applied Sciences and Arts Western Switzerland, Geneva, Switzerland; 2Department of Epidemiology, Research Line Functioning and Rehabilitation, CAPHRI, Maastricht University, Maastricht, the Netherlands; 3Department of Internal Medicine Specialties, University Hospitals and University of Geneva, Geneva, Switzerland; 4Department of Internal Medicine, Rehabilitation and Geriatrics, University Hospitals and University of Geneva, Geneva, Switzerland; 5Division of Bone Diseases, Department of Medicine, University Hospitals and University of Geneva, Geneva, Switzerland; 6School of Health Sciences, ARC Santé, HES-SO University of Applied Sciences and Arts Western Switzerland, Neuchâtel, Switzerland; 7Department of Thoracic Surgery, University Hospitals and University of Geneva, Geneva, Switzerland; 8School of Health Sciences, HES-SO Valais-Wallis, University of Applied Sciences and Arts Western Switzerland, Valais, Switzerland; 9Department of Community Medicine, University Hospitals and University of Geneva, Geneva, SwitzerlandCorrespondence: Simone Chantal Gafner Rue des Caroubiers 25, CH-1227 Carouge, Geneva, SwitzerlandTel +41 22 388 34 70Fax +41 22 388 34 24Email simone.gafner@hesge.chBackground/Objectives: Early detection of fall risk in persons older than 65 is of clinical relevance, but the diagnostic accuracy of currently used functional tests (eg short physical performance battery [SPPB] and timed up and go test [TUG]) to assess older persons’ fall risks remains moderate. Recent literature highlights the importance of strong hip abductors to prevent falls. We thus aimed to assess the diagnostic accuracy of hip abductor strength measures to assess older persons’ fall risks.Methods: Hip abductor maximum voluntary isometric strength (ABD MVIS), rate of force generation (ABD RFG), and the SPPB and TUG functional fall risk assessments were assessed in 60 persons aged over 65 years (82.0 ± 6.1 years). The diagnostic accuracy (area under the curve [AUC], sensitivity [sens], specificity [spec], positive predictive value [PPV], negative predictive value [NPV], and positive and negative likelihood ratios [LR+, LR−]) was evaluated at a clinically important 90% sensitivity level. Cut-off values for clinical use were calculated.Results: In our population, hip ABD MVIS (AUC 0.8, sens 90.6%, spec 57.1%, PPV 70.7%, NPV 84.2%, LR+ 2.1, LR- 0.2, and cut-off value ≤ 1.1 N/kg) and hip ABD RFG (AUC 0.8, sens 90.6%, spec 46.4%, PPV 65.9%, NPV 81.3%, LR+ 1.7, LR- 0.2, and cut-off ≤ 8.47 N/kg/s) show diagnostic accuracy comparable to other fall risk assessments (SPPB and TUG) and a high net sensitivity when used in a test battery.Conclusion: Hip ABD MVIS or RFG shows good diagnostic accuracy to differentiate between older fallers and nonfallers compared to the chosen external criterion history of falls. The high net sensitivity when hip ABD MVIS or RFG is combined with currently used fall risk assessments shows promise in contributing value to a test battery and should be investigated further in longitudinal studies.Keywords: measurement study, muscle strength, hip, functional performance, accidental falls, aged